2007
DOI: 10.4103/0973-1482.31970
|View full text |Cite
|
Sign up to set email alerts
|

Serous papillary adenocarcinoma of the rete testis: Unusual ultrasonography and pathological findings

Abstract: We report a case of serous papillary adenocarcinoma of the rete testis in a 22-year-old man. Adenocarcinoma of the rete testis is highly resistant to radiotherapy and any known chemotherapeutic regimen. We recommend radical orchiectomy At last follow up, the patient was well, without any evidence of recurrence, ten years after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Adenocarcinoma of the rete testis is typically located in the region of the epididymis or testicular hilum, rather than the intratesticular region, as reported in the majority of the current literature (3,8,13,14). The majority of patients exhibit hydrocele, and echoic paratesticular regions are observed (3,15,16).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Adenocarcinoma of the rete testis is typically located in the region of the epididymis or testicular hilum, rather than the intratesticular region, as reported in the majority of the current literature (3,8,13,14). The majority of patients exhibit hydrocele, and echoic paratesticular regions are observed (3,15,16).…”
Section: Discussionmentioning
confidence: 92%
“…In the majority of cases, the lesions present as hypoechoic masses with poorly-defined borders, although an uneven echo pattern is detected on occasion (3,9). Increased vascularization of the tumor is another ultrasonographic feature which is helpful in differential diagnosis (8). The case presented in the current report is in accordance with the majority of these features.…”
Section: Discussionmentioning
confidence: 99%
“…Serous tumours of the testis and paratestis are rare, with fewer than 50 cases reported in the literature [1, 2, 3]. These tumours usually occur in young to middle-aged adults and typically present as a testicular mass [4].…”
Section: Discussionmentioning
confidence: 99%
“…Serous tumours are the most common subtype, but these remain rare with fewer than 50 cases reported in the literature so far [1, 2, 3]. We report a case of a young man diagnosed with serous carcinoma of the testis, occurring 18 years after first diagnosis of a testicular germ cell tumour in the contralateral testis.…”
Section: Introductionmentioning
confidence: 99%
“…So that we can address this question, we reviewed the literature on serous tumours of the testis, and identified 38 neoplasms . In contrast to the ovary, where high‐grade tumours represent the most common type, we found that 22 of the testicular neoplasms showed features of borderline serous tumour, and five of the remaining invasive neoplasms contained borderline areas, consistent with low‐grade serous carcinoma.…”
Section: Acknowledgementsmentioning
confidence: 96%